How to weigh a donkey in the Kenyan countryside. Issue 4 (October 2014) - Milner, Kate; Rougier, Jonathan
<x xml:space="preserve">Abstract</x> Donkeys play a crucial role in the lives of rural Kenyans. When they fall sick, vets need a quick and accurate method of weighing the animals to administer the right dosage of drugs. The humble nomogram can help, as Kate Milner and Jonathan Rougier explain.